2010
DOI: 10.1590/s0102-09352010000600012
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do estradiol e da progesterona no desenvolvimento e na qualidade de embriões bovinos produzidos in vitro

Abstract: RESUMOAvaliaram-se o desenvolvimento e a qualidade de embriões bovinos, cocultivados com células epiteliais do oviduto bovino (CEOBs) expostas ou não ao estradiol e à progesterona. Os ovócitos foram maturados in vitro por 24h e, então, fertilizados utilizando-se sêmen congelado, em estufa de CO 2 a 5% e 38,5 o C. As CEOBs foram cultivadas em TCM-199 com ou sem estradiol (E 2 ) (24 horas), nas mesmas condições da maturação e fertilização in vitro (MIV e FIV), e, em seguida, adicionadas aos diferentes grupos em … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Another important factor that may significantly affect their activity is the presence of hormones. It has been known that treatment of BOEC with estradiol alone or in combination with progesterone increases the quality of embryos produced in vitro (42). Thus, further studies should be designed to mimic an in vivo environment with the presence of hormones at specific phases.…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor that may significantly affect their activity is the presence of hormones. It has been known that treatment of BOEC with estradiol alone or in combination with progesterone increases the quality of embryos produced in vitro (42). Thus, further studies should be designed to mimic an in vivo environment with the presence of hormones at specific phases.…”
Section: Discussionmentioning
confidence: 99%
“…Matsuo et al (78) used a 3-step oocyte culture system that mimicked temporal physiological changes in E 2 and P 4 , and reported that the treatment enhanced in vitro embryo development reflected as a greater blastocyst formation rate. Reis et al (79) cultured zygotes in the following groups (concentrations in μg/mL): control, 1 E 2 + 100 P 4 , 1 E 2 , and 100 P 4 . The authors reported that E 2 and P 4 together and E 2 alone resulted in greater hatching rates and improved embryo quality.…”
Section: Evidence On the Effect Of Hormonesmentioning
confidence: 99%